Reclaimed and Up‐Cycled Cathodes for Lithium‐Ion Batteries. Issue 12 (9th June 2022) - Gastol, Dominika; Marshall, Jean; Cooper, Elizabeth; Mitchell, Claire; Burnett, David; Song, Tengfei; Sommerville, Roberto; Middleton, Bethany; Crozier, Mickey; Smith, Robert; Haig, Sam; McElroy, Con Robert; et al.
Abstract: As electric vehicles become more widely used, there is a higher demand for lithium‐ion batteries (LIBs) and hence a greater incentive to find better ways to recycle these at their end‐of‐life (EOL). This work focuses on the process of reclamation and re‐use of cathode material from LIBs. Black mass containing mixed LiMn2 O4 and Ni0.8 Co0.15 Al0.05 O2 from a Nissan Leaf pouch cell are recovered via two different recycling routes, shredding or disassembly. The waste material stream purity is compared for both processes, less aluminium and copper impurities are present in the disassembled waste stream. The reclaimed black mass is further treated to reclaim the transition metals in a salt solution, Ni, Mn, Co ratios are adjusted in order to synthesize an upcycled cathode, LiNi0.6 Mn0.2 Co0.2 O2 via a co‐precipitation method. The two reclamation processes (disassembly and shredding) are evaluated based on the purity of the reclaimed material, the performance of the remanufactured cell, and the energy required for the complete process. The electrochemical performance of recycled material is comparable to that of as‐manufactured cathode material, indicating no detrimental effect of purified recycled transition metal content. This research represents an important step toward scalable approaches to the recycling of EOL cathode material in LIBs. Abstract : Black mass containing mixed LiMn2 O4 and Ni0.8 Co0.15 Al0.05 O2 from a Nissan Leaf pouch cell is recovered via two different recycling routes, shredding or disassembly. The reclaimed material is further treated to reclaim the transition metals salts. Upcycled LiNi0.6 Mn0.2 Co0.2 O2 (NMC 622) is produced. The energy inputs of the processing, purity, and performance of the NMC 622 from the two processes are evaluated.